Range of Motion (ROM) Exercise Assistance Program and Providing Warm Red Ginger Compresses to reduce Knee Pain for the Elderly in the Melur Community Health Center Work Area - Syafrisar Meri Agritubella; Yoza Misra Fatmi; Rahimatul Uthia (Universitas Lancang Kuning, 2023)
Knee joint pain in the elderly has hampered physical activity, mobilization and caused the elderly to be in a group with a high level of dependence on family. The purpose of this community service activity is to help the elderlyindealing with knee joint pain independently by doing ROM Exercise and warm red ginger compresses at home. The method used is providing health education and teaching the elderly to do ROM Exercise and Compress Red Ginger stew on the knees. The activity was carried out in 6 visits consisting of 1 visit in the Meeting Hall starting with providing education about osteoarthritis and how to deal with joint pain which was attended by 15 people consisting of 10 elderly people and 5 posyandu cadres. Furthermore, 4 home visits were made to 10 elderly who experienced knee join pain. The last visit was monitoring and evaluation of the implementation 1 time. The results showed that 100% of the elderly were able to do ROM independently. The average decrease in pain scale after being given warm red ginger compresses and ROM was 1,6. Suggestions are that cadres can remind theelderly to do regular and independent joint motion exercises so that the level ofdependence on the family can be reduced and the elderly are able to carry out their daily activities.